THE MOTIVATION FOR PARENTHOOD AND MARITAL FUNCTIONALITY–THE DIFFERENCES DEPENDING ON THE TRIMESTER OF PREGNANCY - Jestrović, Jovana; Mihić, Ivana (Psihološka istraživanja, 2018)
The aim of this study was to describe the differences in the motivation for parenthood among pregnant women in different trimesters of pregnancy and with different marital functionality. Therefore, 63 first time pregnant women, 30 years old on the average, completed the questionnaire on their demographic characteristics, the modified version of the Parental Motivation Scale and the Dyadic Adjustment Scale. The most common motive for parenting is the motive of care, followed by social pressure, while the least common is the motive of continuity.The results were analysed using MANCOVA, with different forms of motivationserving asdependent variables, the trimester as thecategorical independent variable and the dimensions of marital functionality as covariates. The higher motive of care was found among the respondents who estimated that the tension but also the cohesiveness in their marriage was lower.On the other hand, therespondents who wereless satisfied with marriage exhibitedmore pronounced external forms of motivation. Regardless of the fact that the inner motive wasthe most prevalent inthe analysed sample, the obtained results point to potential risks in the followingstages of family development, since the arrival of the child may bring about a further decrease in the satisfaction with the marriage and partners’ participation in the joint activities.